Anaesthesia and perioperative incident reporting systems: Opportunities and challenges. Issue 1 (May 2021) - Arnal-Velasco, Daniel; Barach, Paul
Abstract : Incident Reporting Systems (IRS) continue to be an important influence on improving patient safety. IRS can provide valuable insights into how to prevent patients from being harmed at the organizational level. But inadequate expectations and misuse, for performance assessment, patient safety measurement or research, have hindered the full IRS potential. Health care organizations need to develop effective strategies built on trust and truth telling to improve the impact of IRS. This requires strategies to address the limited resources to analyse the near-misses or adverse events; avoid the punitive drift through maintaining the anonymity and protective legislation; integrating IRS and avoiding its confusion with mandatory adverse event response systems; training data analysts to focus on the system instead of the individual through a balanced simple taxonomy; combine the analyses at the local level, to reinforce effective and personalized feedback, with the potential of a national or supranational learning platform.